Implementation of a methodology for analysis of gross alpha and gross beta, as water potability parameters in Brazil, and 226Ra, 228Ra and 210Pb for radiological water monitoring - Christina de Albuquerque Ferreira; Felipe Juvêncio Dias; Bruna de Lima Sá; Mariana R. Monteiro; Edson Felipe de Souza Ladeira; Hamilton Pires Barbosa Mendes; Richard Secioso Guimarães; Ronaldo Leão Guimarães; Inaya Correa Barbosa Lima; Ademir Xavier da Silva (Brazilian Journal of Radiation Sciences, 2025)
In order to guarantee the quality and safety of water intended for human consumption in Brazil, the GM/MS Regulation No 888, of 4 May 2021, of the Ministry of Health, establishes parameters, through laboratory analyses, to monitor substances that pose a risk to human health. As far as radiological standards are concerned, the activity concentration limits must not exceed 0.5 Bq/L for gross alpha and 1.0 Bq/L for gross beta. In the case of alpha/beta values exceeding the maximum permitted value, other natural and/or artificial radionuclides present in the water must be quantified. The radionuclides most likely to be found in water intended for human consumption are radium and uranium, which are the main fractions of the doses received by man from internal emissions derived from radium, 226Ra and its decay products. In order to comply with environmental regulations and to be a conformity assessment organism, competent to carry out ionizing radiation tests, necessary for the monitoring of drinking water in Brazil; the Centro de Biologia Experimental Oceanus laboratory, located in Rio de Janeiro, carried out gross alpha and gross beta analyses, using the gas flow proportional counter technique; a the analyses of 226Ra, 228Ra and 210Pb, using the radiochemical separation technique, followed by alpha/beta counting; in water for human consumption. It was necessary to obtain results on the equipment's operating plateau, background, efficiency and factors related to the attenuation effect of alpha counts. The laboratory has demonstrated the reliability of its results by participating in the National Intercomparison Programme - PNI, and by requesting for accreditation from the Brazilian Network of Testing Laboratories - RBLE, according to the ABNT ISO/IEC 17025 standard; in the category of ionising radiation tests.